Peranan Majelis Pengawas Wilayah atas Penjatuhan Sanksi Terhadap Notaris yang Tidak Membacakan Akta - Arifani Kurnia (Universitas Islam Indonesia, 2017)
The problems in this research include, first, what is the role of the Regional Notary Supervisory Council in imposing sanctions on notaries who do not read deeds? Second, what is the legal consequence for a notary who does not read the deed based on the Decision of Yogyakarta Regional Supervisory Council Number 03/Pt/Mj.PWN DDIY/VI/2016? and third, what is the legal consideration of Yogyakarta Regional Supervisory Council in imposing sanctions on the notary? This study is normative-empirical legal research with a field research type. The results indicate that, first, the role of Notary Supervisory Council is to protect the interests of the community or parties who suffer losses due to legal actions by irresponsible notaries who conduct their duties without referring to the stipulated provisions in both the law and decisions of the notary professional association/organization. Second, the legal consequence for the notary based on the Decision of Yogyakarta Regional Supervisory Council Number 03/Pts/Mj.PWN DIY/VI/2016 is in the form of written notice in which the decision can be used as a reason for a case reporter to sue the concerned notary for a civil compensation. Third, the legal basis for imposing sanctions on the notary, which is the result of investigation stating that the notary has been found guilty, is not a violated formal requirement.Keywords: Notary; deed; notary supervisory council